We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
1
3697
1
avatar

Cos^2x=(1-sinX)(1+sinX)

 Aug 20, 2015

Best Answer 

 #1
avatar+8519 
+5

Hallo anonymous!

 

That is the trigonometric Pythagoras

 

sin²x + cos²x = 1

cos²x = 1 - sin²x        →           3. binomial theorem

cos²x = (1 - sinx) * (1 + sinx)

 

Greetings asinus  :- )

 Aug 20, 2015
 #1
avatar+8519 
+5
Best Answer

Hallo anonymous!

 

That is the trigonometric Pythagoras

 

sin²x + cos²x = 1

cos²x = 1 - sin²x        →           3. binomial theorem

cos²x = (1 - sinx) * (1 + sinx)

 

Greetings asinus  :- )

asinus Aug 20, 2015

32 Online Users

avatar
avatar
avatar
avatar
avatar
avatar
avatar